Correlation of Net Atrioventricular Compliance with the Outcome of Successful Percutaneous Transvenous Mitral Valve Commissurotomy (Cardiovascular Journal, 2016)
Background: In patients with mitral stenosis the prognostic significance of net atrioventricular compliance has already been established. It was found that left atrial compliance significantly improve immediately after successful balloon mitral valvotomy. This study was conducted to evaluate the immediate improvement of atrioventricular compliance following percutaneous Transvenous mitral commissurotomy (PTMC) & to see the relation of post PTMC atrioventricular compliance with immediate clinical & other echocardiographic outcomes.Methods: This prospective observational study was undertaken in the Department of Cardiology, National Institute of Cardiovascular diseases, Dhaka. A total of 50 patients who had had successful PTMC were selected. All patients were evaluated clinically and echocardiographically 24 hours before PTMC, immediately after PTMC and 72 hours after PTMC.Results: Atrioventricular compliance improved significantly following PTMC (mean Cn 3.42 ± 1.64ml/mm Hg vs. 6.38 ± 2.81ml/mm Hg, p4 ml/mm of Hg and patients with atrioventricular compliance d4ml/mm of Hg. NYHA class for heart failure, transmitral peak and mean pressure gradient, pulmonary artery systolic pressure were negatively correlated to atrioventricular compliance. Index left atrial anteroposterior diameter had no significant correlation with atrioventricular compliance.Conclusion: Successful PTMC is associated with immediate significant improvement in atrioventricular compliance. Atrioventricular compliance is inversely correlated with NYHA functional status, transmitral pressure gradient & pulmonary artery systolic pressure following successful PTMC. Post PTMC atrioventricular compliance is also positively correlated with pre PTMC atrioventricular compliance.Cardiovasc. j. 2016; 8(2): 99-109